Analisis Penggunaan Model Berbasis Proyek (PJBL) Project Based Learning Dalam Meningkatkan Hasil Belajar Siswa di Sekolah Dasar - Nur Annisa Mahmudah; Ahmad Suriansyah; Wahdah Refia Rafianti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Project Based Learning (PjBL) is considered an effective alternative in overcoming problems with student learning outcomes. This model plays an active role in the learning process because it provides opportunities for students to learn through direct experience, collaboration, and application of knowledge in real-world contexts. The research aims to analyze the effectiveness and level of student achievement and the influence of implementing the PjBL model on student learning outcomes in elementary schools through the implementation of the PjBL model. The method used in this research is a literature review from electronic databases, one of which is Google Scholar. Based on the articles collected, the use of the PjBL model can improve student learning outcomes. The effectiveness of using the PjBL model can be seen from the presentation of the average learning outcomes, before using PjBL it was 25%, then there was an increase after using the PjBL model in cycle 1, 60%, cycle 2, 75%, and cycle 3, 90%. Based on these data, the use of the PjBL model can improve student achievement and learning outcomes.